PELATIHAN BELAJAR AL QUR’AN DENGAN BAIK DAN BENAR DALAM MENINGKATKAN PEMAHAMAN ANAK - Bahtiar, Yuyun; Agustin, Ulfa Wulan; Ma'arif, Iin Baroroh; Afidah, Nurul; Nur, Luluk Choirun Nisak (ABIDUMASY, 2025)
Training to learn the Al-Qur'an properly and correctly plays an important role in improving children's understanding of Islamic teachings. This training program aims to equip children with the ability to read, understand, and apply the Al-Qur'an properly. The approach method used in the community service activities of this community partnership program includes the SL (Service Learning) method. This method is an approach that connects learning with real experiences in the community. With an interactive and fun approach, this training not only improves the technical ability to read the Al-Qur'an but also instills children's love for the holy book and Islamic teachings. The results of the training showed a significant increase in children's ability to read the Al-Qur'an and their understanding of the content and meaning of the verses read. This study highlights the importance of good and correct religious education from an early age to form a strong character and religious understanding.